Service quality and customer satisfaction: a case study of customer service in Jabatan Pengangkutan Jalan (JPJ) WPKL / Mohd Iskandar Lamat - Lamat, Mohd Iskandar (2016)
The issue of this report is the customer service of Jabatan Pengangkutan Jalan (JPJ) WPKL which is based on the services given by JPJ WPKL customer service section that I have been position on my bachelor practicum on 26 January 2016 until 13 May 2O16.The purpose of this study is to examine the customer service or corporate communication department from JPJ WPKL services to their customers at the counter, telephone-mail and etc. The methodology to gain the data is by observing all the service quality and customer satisfaction towards JPJ WPKL customer service workforce given to its entire customers from all the segments of customer service. The observation is supported by the secondary data from the section data to complete an efficient report. The expected finding from this study is to gain knowledge on how the service quality of JPJ WPKL customer service can influence customer satisfaction and also to recommended new and more effective customer service for the company to be more successful in the business.